Rancang Bangun Miniatur Stasiun Cuaca Untuk Monitoring Curah Hujan, Suhu Dan Kelembaban Udara Area Lokal Menggunakan Berbasis IOT - Refi Amalianti; Abdul Jabbar Lubis; Imran Lubis (Universitas Harapan Medan, 2021)
News or news about the weather becomes a common necessity at this time, because many activities depend on weather conditions. Weather news that is commonly used daily is temperature, humidity, and rainfall. In this weather monitoring process utilizing IoT as a concept whose purpose is to expand the benefits of continuously connected internet connectivity, and also users can build their own information network including building their own weather monitoring system that can be used in the desired local area, which is used to observe weather conditions in residential or local areas, Because there is often a difference in weather between one area and another.From these problems came the idea to create a tool